2023
DOI: 10.3390/agronomy13030835
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Study of Garlic Root Cutting Based on Continuous Force Feedback

Abstract: In this study, we quantified and analyzed the root-cutting process of garlic with a test bench with pressure sensors on the basis of the comparative analysis of various information perception methods. On the basis of the output value of the pressure sensor, the force curve of garlic roots was plotted, and the double round blade cutting module is optimized on the basis of the force curve diagram. The innovative proposal of slotted round blades for garlic root cutting is presented here. The round blade diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…When analyzing Expression (15), it can be argued that at the moment the particle enters the thrower blade and at the initial stage of the particle movement along the blade, while its relative velocity .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When analyzing Expression (15), it can be argued that at the moment the particle enters the thrower blade and at the initial stage of the particle movement along the blade, while its relative velocity .…”
Section: Methodsmentioning
confidence: 99%
“…x will decrease, which means that, according to (15), force F nx will also decrease; that is, the influence of the airflow will weaken.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The issues related to the motion and sliding of particle M along the surface of the working parts of agricultural machines are partly considered in works [33][34][35][36], but no attention is paid to the influence of the external environment in which the particle is moving.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [12] designed a single-row cabbage harvester with two symmetrical disctype cutting knives to cut cabbage roots and determined suitable working parameters to ensure the stability of root cutting. Yang et al [13] found that slotted circular blades with beveled edges cut garlic roots better and optimized the double circular blade cutting module by experiment. Hou et al [14] designed a disc-type castor cutting device and optimized the tool parameters using simulation tests.…”
Section: Introductionmentioning
confidence: 99%